2015
DOI: 10.1016/j.physbeh.2015.02.050
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary CRH-binding protein and stress in female mice

Abstract: The CRH-binding protein (CRH-BP) binds CRH with very high affinity and inhibits CRH-mediated ACTH release from anterior pituitary cells in vitro, suggesting that the CRH-BP functions as a negative regulator of CRH activity. Our previous studies have demonstrated sexually dimorphic expression of CRH-BP in the murine pituitary. Basal CRH-BP expression is higher in the female pituitary, where CRH-BP mRNA is detected in multiple anterior pituitary cell types. In this study, we examined stress-induced changes in CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 64 publications
4
15
0
Order By: Relevance
“…A restraint stress test was performed to evaluate hypothalamic and pituitary function in control rats and both groups of TBT-treated rats. Similar to the findings of Stinnett et al (83) and Felszeghy et al (52), we observed that restraint stress was associated with an increase in CRH expression and plasma ACTH levels in all rats analyzed. However, both groups of TBT rats exhibited elevated CRH expression and increased ACTH levels in response to stress within 30 minutes, thus demonstrating that HPA activity was abnormal.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A restraint stress test was performed to evaluate hypothalamic and pituitary function in control rats and both groups of TBT-treated rats. Similar to the findings of Stinnett et al (83) and Felszeghy et al (52), we observed that restraint stress was associated with an increase in CRH expression and plasma ACTH levels in all rats analyzed. However, both groups of TBT rats exhibited elevated CRH expression and increased ACTH levels in response to stress within 30 minutes, thus demonstrating that HPA activity was abnormal.…”
Section: Discussionsupporting
confidence: 92%
“…In a previous study, we reported an increase in lipid droplet accumulation and PPAR␥ protein expression in the liver in TBT15D rats (31). The accumulation of adrenal lipid droplets is associated with an early steroidogenic pathway blockade and/ or abnormal StAR functioning (83,104). However, it is possible that TBT affects adrenocortical function, leading to abnormal StAR or other steroidogenic enzyme function.…”
Section: Discussionmentioning
confidence: 91%
“…Thus, the presence of a functional CRF-BP particularly in the BNST helps to end the stress response and returns the system to homeostasis, which guarantees a fast resumption of appropriate levels of maternal care. Given that the CRF-BP is up-regulated by acute stressor exposure (Herringa et al, 2004;McClennen et al, 1998;Stinnett et al, 2015), we suggest that its release in the BNST is induced by exposure to the maternal defense test. This up-regulation is certainly important to protect the dam from potentially elevated levels of CRF, which are detrimental for the appearance of maternal behavior (D'Anna and Gammie, 2009;Gammie et al, 2004;Klampfl et al, 2014Klampfl et al, , 2016Klampfl et al, 2013;Pedersen et al, 1991).…”
Section: Accepted Manuscriptmentioning
confidence: 87%
“…Deletion of the CRF-BP gene results in increased anxiety-related behavior (Karolyi et al, 1999) and impaired maternal aggression in lactating female mice (Gammie et al, 2008). CRF-BP deficient mice also show an impaired return to homeostasis after prolonged lipopolysaccharide stress, while basal hypothalamo-pituitary-adrenal axis activity appears normal (Karolyi et al, 1999;Seasholtz et al, 2001;Stinnett et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Although broadly considered a potent enhancer of Ido1 expression in vivo , LPS increases the production of multiple factors (cytokines and stress hormones/corticosteroids) which may be involved in inflammation-induced behaviors (Dantzer et al, 2008; Dantzer et al, 1999). Corticosteroid levels are also acutely elevated following LPS administration (Stinnett et al, 2015; Sulakhiya et al, 2016). We recently reported that the synthetic glucocorticoid-receptor agonist Dex enhanced the ability of IFNγ to induce Ido1-FL (Brooks et al, 2016b), suggesting that stress and inflammation work together to elevate central Ido1.…”
Section: Discussionmentioning
confidence: 99%